Analisis Framing Pemberitaan Ganjar Pranowo Menolak Kehadiran Timnas Israel di Indonesia pada Mediaindonesia.com - Imelda Dwi Putri Nainggolan; Catur Suratnoaji (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
Ahead of the 2024 presidential election, Nasdem has nominated Prabowo as a presidential candidate. On the other hand, Ganjar Pranowo has also been promoted by a number of parties so that Prabowo and Ganjar must compete in a healthy manner. In 2023, Ganjar was discussed by various media because Ganjar participated in rejecting Israel's presence to play in the 2023 U-20 World Cup which caused Indonesia to fail to host. As a result, Ganjar received a lot of negative comments. As a Nasdem cadre and owner of the mediaindonesia.com portal, Surya Paloh has the power to regulate how news is framed regarding issues facing Ganjar for personal political gain. Therefore, this study aims to determine the framing analysis of Ganjar Pranowo's news in rejecting the presence of the Israeli national team in Indonesia on mediaindonesia.com. This study uses a qualitative approach with observational data collection techniques and framing analysis using the Robert N. Entman model. There are four elements used in the Entman model, namely Problem Identification, Causal Interpretation, Moral Evaluation, and Treatment Recommendations. The conclusion of this study is that Mediaindonesia.com is neutral in framing news, Mediaindonesia in framing news provides an opportunity and space for agreement from Ganjar to provide his response and mediaindonesia.com does not provide his statement to lead opinions. Therefore, there is no personal political interest in the way mediaindonesia.com is framed